External Conflict Faced by Main Character In Movie "Monster Hunt": External Conflict - sefin, maria (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
The objective of this study is to analyze the external conflict which is being faced by the Main characters and also analyzing the way to resolve by the conflict main character in movie "Monster Hunt" . Movie has analyzed by using descriptive qualitative method. In analyzing the data two theories related to the topic had been taken namely theory of external conflict proposed by Kenney 1966) used to analyze the external Conflict Faced by Main Character s and theory of management strategy proposed by Thomas and Kilman (1970) used to analyze how are external Conflict resolved by the main character. The result of this study shows that the main character faced the conflict, namely external Conflict, external Conflict occurs between character and outside forces. The way the main character resolve the conflict in movie"Monster Hunt" used for management strategies namely; avoidance, collaborative,compotetive, compromising. Key word Conflict, external and Movie